Implementasi Budaya Kerja Core Value BerAKHLAK pada Aparatur Sipil Negara - Ghea Arnanda; Oktarizka Reviandani (SOCIETAS, 2024)
Problems regarding the lack of collaboration, innovation, and ego between fields that can hinder the productivity of ASN performance. The East Java Provincial Government seeks to carry out bureaucratic reforms, one of which is to create an accountable government and is oriented towards changing effective daily work behavior by creating deep-rooted work culture values and ensuring that ASN complies with these values. This study aims to analyze the extent to which the implementation of ASN BerAKHLAK core values in the Bureau of Organization of the Regional Secretariat of East Java Province has been implemented. This research uses a qualitative and descriptive approach. The data analysis techniques used were data collection, data condensation, data presentation, and conclusion drawing. Data collected through interviews, observation, documentation, literature study and official documents of related agencies. The results of the research are based on the seven values of BerAKHLAK work culture, namely Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative. The results showed that the implementation of the seven work culture values at the Bureau of Organization of the Regional Secretariat of East Java Province was carried out well as expected and was able to increase the productivity of ASN employee performance. Proven by providing services according to edicts, complying with the ideology of Pancasila, Sharing Knowledge, collaborative ASN Learning, innovations that support the implementation of tasks, namely the BerAKHLAK application, SI MAS BAIK, SuKMA e-Jatim. In addition, creating a GEMESPUL work environment, BU TATIK, paperless and the development of a corruption-free integrity zone